(untitled) (Dhaka University Journal of Biological Sciences, 2018)
A pot-culture experiment was conducted to investigate phytoavailability of chromium in inorganic chromium salt and raw poultry feed made from tannery waste. Poultry feed from tannery waste was applied to the soil at a rate of 5 t/ha while inorganic chromium salt was applied at a rate of 10 mg/ kg and 810 mg/kg. An upland leafy-vegetable commonly known as Kalmi (Ipomoea aquatica) was used to assess the phytoavailability. Physico-chemical analyses of all soil and plant samples were done at 0, 15, 30 and 45 days of incubation to assess chromium phytoavailability and also its effects on the uptake of other heavy metals viz., lead and iron. Plants treated with Cr showed declined vegetative growth, low accumulation of dry matter, reduced nutrient concentration and reduced nutrient uptake. It was found that the plants accumulated higher amount of Cr from raw poultry feed treated soil compared to that of the inorganic Cr salt treated soil. The effect of treatments on Cr accumulation both in root and shoot was found significant. The study concludes that Cr is phytoavailable depending on the source and increased concentration of Cr decreases accumulation of Pb and Fe and thereby likely to decrease uptake of these metals. Dhaka Univ. J. Biol. Sci. 27(2): 201-211, 2018 (July)